To study the epidemiology of various sexually transmitted diseases in tribal area of Valsad - Shah, Bhuvnesh Girish; Sheth, Keya Jayesh (International Journal of Research in Dermatology, 2017)
Background: Sexually transmitted diseases have been considered as a major health problem, in developing countries. With up springing of HIV and AIDS, the attention and importance of STDs have again come into limelight. Epidemiological study is needed to understand the pattern of various STDs prevalent in tribal place of Valsad. Methods: The epidemiological pattern of around 1012 patients have been studied. Patients were followed up at regular interval. Results: 33.3% were males and 66.6% were females. Out of these major percentage of patients had reported vaginal discharge (27.7%), followed by genital warts (23.6%). Females were reluctant to consult the doctor for their problem. (72%) were married and (27.7%) were unmarried. No contraceptive measures were taken in 50% cases. 20 cases of pregnancy with STDs were studied. Conclusions: A epidemiology study was taken up to understand the nature, type and extend of sexually transmitted diseases in the tribal population. Also to know the understanding amongst the masses about the STDs especially in teenagers and young people.